2021
DOI: 10.3390/ma14051058
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultrasonic Non-Contact Air-Coupled Techniques for Characterization of Impact-Type Defects in Pultruded GFRP Composites

Abstract: This article compares different air-coupled ultrasonic testing methods to characterize impact-type defects in a pultruded quasi-isotropic glass fiber-reinforced plastic (GFRP) composite plate. Using the air-coupled transducers, comparisons among three methods were performed, namely, bulk-wave through transmission, single-side access using guided waves, and ultrasonic-guided wave tomography. The air coupled through transmission technique can determine the size and shape of impact-type defects with a higher reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Non-destructive tests are also used to test the elastic properties of composite materials [ 34 , 35 ]. The through-transmission method as well as the Phased Array (PA) method make it possible to detect defects inside composite materials [ 36 ]. Previous studies have demonstrated that defect orientation can have a significant impact on its detection.…”
Section: Introductionmentioning
confidence: 99%
“…Non-destructive tests are also used to test the elastic properties of composite materials [ 34 , 35 ]. The through-transmission method as well as the Phased Array (PA) method make it possible to detect defects inside composite materials [ 36 ]. Previous studies have demonstrated that defect orientation can have a significant impact on its detection.…”
Section: Introductionmentioning
confidence: 99%
“…Cerniglia [ 9 ] proposed a laser ultrasonic technique for the in-line inspection of laser powder deposition components. Asokkumar [ 10 ] compared different air-coupled ultrasonic testing methods to characterize impact-type defects in a pultruded quasi-isotropic GFRP composite plate. However, this method is not suitable for the carbon fiber rod with the irregular interlayer interface.…”
Section: Introductionmentioning
confidence: 99%
“…The second approach is connected with the use of an array of piezoelectric transducers, acting as both actuators and sensors, attached to selected points on an analysed structure. Wave propagation signals are collected and then processed using appropriate damage detection algorithms such as the time of flight (TOF) based triangulation method [ 3 ], supported by ellipse or hyperbolic probability imaging [ 4 , 5 ], the time-reversal technique [ 6 ], the migration technique [ 7 ], phased-array beamforming [ 8 ] and finally ultrasound tomography, widely used for inspection of structures made of concrete [ 9 , 10 , 11 ], metal [ 12 , 13 , 14 ] and composite materials [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%